Purjehtijat - Kailas, Uuno, 1901-1933 (Salt Lake City, UT : Project Gutenberg, 2023)
"Purjehtijat" by Uuno Kailas is a collection of poetic works written during the early 20th century. This book features a variety of themes and styles, showcasing the author's reflections on life, nature, love, and spirituality. The poems present a rich tapestry of imagery and emotion, likely drawing on both personal experience and universal human truths. The collection includes a range of verses that evoke a sense of wonder and contemplation. In pieces like "Purjehtijat," which translates to "The Sailors," Kailas explores existential themes, likening life to a perilous journey across the sea, fraught with challenges and uncertainties. Other poems, such as "Eeva" and "Atlantis," delve into love and loss while capturing the beauty of the human experience. Overall, the book invites readers to reflect on their own journeys, connecting deeply with nature and the intricate emotions that shape our lives. (This is an automatically generated summary.)
Release date is 2023-09-14
Tapio Riikonen
Keywords: Finnish poetry -- 20th century